Component resolved diagnosis and risk assessment in food allergy: Molecular diagnosis in food allergy - Martelli, Alberto; Calvani, Mauro; Foiadelli, Thomas; Tosca, Mariangela; Pingitore, Giuseppe; Licari, Amelia; Marseglia, Alessia; Ciprandi, Giorgio; Caffarelli, Carlo (Acta Biomedica Atenei Parmensis, 2021)
Allergy testing should only be performed in the context of the clinical history as history provides the cornerstone of diagnosis. In food allergy, some allergy tests often give rise to false positive results and thus can lead to unnecessary avoidance or delay on foods introduction. The use of Component Resolved Diagnosis in combination with conventional sensitization testing improves analytical and diagnostic performance and can lead to the reduction of diagnostic oral food challenges. Component Resolved Diagnosis can be helpful in identifying some risks for the allergic child. Molecular diagnosis can help also in predicting the development of the allergy march, in severe reactions (lipid transfer protein, seed storage proteins, etc.) in food allergy and for potential clinical cross-reactivity.